Answer:
209.66 m
Step-by-step explanation:
Given:
Original length of the spaceship, L = 481 m
Speed of the spaceship, v = 2.70 × 10⁸ m/s
Now,
using the concept of length contraction, we have
![L=\frac{L'}{\sqrt{1-(v^2)/(c^2)}}](https://img.qammunity.org/2020/formulas/physics/college/f1nb8g1c7hnt8s29q5il7jwdv5fyila4wc.png)
where,
L' is the observed length
c is the speed of the light
Thus,
on substituting the respective values, we get
![481=\frac{L'}{\sqrt{1-((2.70*10^8)^2)/((3*10^8)^2)}}](https://img.qammunity.org/2020/formulas/physics/college/1n3h575oscinfpfxzhn7zwwzeaqzckg5ce.png)
or
L' = 209.66 m